Toward a feminist philosophy of economics - Barker, Drucilla K., 1949-; Kuiper, Edith, 1960- (Economics as social theory., 2003)
This book edited by two of the most respected figures in feminist economics is a welcome collection that charts and critically analyses how other movements have influenced the development of feminist economics as a distinct discipline.